Simultaneous Separation and Determination of 14C and 3H in Spent Resins from PWR Nuclear Power Plants - 박순달; 김정석; 김종구; 한선호; 지광용; Soon-Dal Park; Jung-Suck Kim; Jong-Goo Kim; Sun-Ho Han; Kwang-Yong Jee (Journal of nuclear fuel cycle and waste technology (Online), 2007)
가압경수로형 원자력발전소의 운영과정에서 발생된 폐수지내 및 의 분포특성을 조사하였다. 표준용액을 사용한 의 회수율 측정결과, 사용한 산의 종류에 관계없이, 3 N-HCl , 주입한 농도 범위에서 의 회수율을 나타내었다. 같은 장치를 사용하여 HTO 표준용액 증류에 의한 의 회수율은 주입한 농도 범위에서 이었다. 습식산화-산용출법에 의한 폐수지의 및 동시분리시, 를 사용했을 때 다른 감마핵종에 의한 방해가 없었으며, 포집액이 섬광제와 잘 혼합되었다. 그러나 3 N-HCl을 사용했을 때 포집용액에서 및 등의 감마핵종이 검출되었다. 또한 Sample Oxidizer에 의한 포집용액에서도 및 등이 검출되었으며, 포집용액에서는 이 검출되었다. 폐수지의 총 함량중 약 70% 이상이 무기 탄소로 확인되었다. 30개 폐수지 시료중 8개 고방사능 폐수지의 및 의 평균농도는 각각 이었으며 22개 저방사능폐수지에서는 각각 이 검출되었다. 고방사능 폐수지의 평균 비는 28로 저방사능 폐수지의 0.70에 비해 높게 나타났으며, 및 의 농도는 서로 비례하는 경향을 보였다. In this work distribution characteristics of spent resins from nuclear power plants(NPPs), pressurized water reactors(PWRs), was investigated. It was found that the recovery percent of by the wet oxidation-acid stripping was for the added activity range of , and it was not affected by the kinds of stripping acids, 3N-HCl, . And the recovery percent of by distillation using the same apparatus was for the added activity range of . Among the tested stripping acids, 3\;N-HCl, , only the trapped solution by distillation in was compatible with the 3H scintillator, Ultimagold XR. Neither of the trapping solutions from the spent ion exchange resin samples by the wet oxidation-3 stripping contained gamma nuclides. However, some gamma nuclides, , were found in the trapped solutions of the spent resins by the wet oxidation-3 N-HCl stripping. It was the same for the trapping solutions of the spent resins by Sample Oxidizer(PACKARD MODEL 307). Meanwhile only two nuclides, , were found in the trapping solutions of the spent resins by Sample Oxidizer(PACKARD MODEL 307). It was found that most of the in the spent resins existed as inorganic carbon form, more than about 70% of the total content. Among the analyzed 30 spent ion exchange resin samples, the average concentration of and for the high radioactive samples, 8 samples, was and that for the low radioactive samples, 22 samples, was , respectively. And the average ratio for the high radioactive samples, was higher, 28, than that of low radioactive samples, 0.70. Some linear relationship trend was found between the activity concentrations of .